Neurospora strains incorporating fluffy, and their use as testers. - D. D. Perkins; B. C. Turner; V. C. Pollard; A. Fairfield (Fungal Genetics Reports, 1989)
We have used fluffy (fl) strains extensively as female parents in mating-type tests and for a variety of other applications where high fertility and absence of conidia are advantageous.